2015
DOI: 10.1016/j.rpor.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Medical physics in radiotherapy: The importance of preserving clinical responsibilities and expanding the profession's role in research, education, and quality control

Abstract: Medical physicists have long had an integral role in radiotherapy. In recent decades, medical physicists have slowly but surely stepped back from direct clinical responsibilities in planning radiotherapy treatments while medical dosimetrists have assumed more responsibility. In this article, I argue against this gradual withdrawal from routine therapy planning. It is essential that physicists be involved, at least to some extent, in treatment planning and clinical dosimetry for each and every patient; otherwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
0
13
0
6
Order By: Relevance
“…The more important question is, however, where will it not (or perhaps should not) do what many are afraid it will — take over the roles and responsibilities of the medical physicist? A fundamental role of the medical physicist is team member — working together with physicians, technologists, nurses, therapists, engineers, and even patients in the effective, efficient, and safe delivery of health care . AI can help provide valuable and accurate information with respect to a multitude of essential care variables (e.g., repeatability and reproducibility; adaptive sequence generation; automated protocolling; assist with smart positioning to decrease retakes; assist with treatment planning).…”
Section: Against the Proposition: Elizabeth A Krupinski Phdmentioning
confidence: 99%
“…The more important question is, however, where will it not (or perhaps should not) do what many are afraid it will — take over the roles and responsibilities of the medical physicist? A fundamental role of the medical physicist is team member — working together with physicians, technologists, nurses, therapists, engineers, and even patients in the effective, efficient, and safe delivery of health care . AI can help provide valuable and accurate information with respect to a multitude of essential care variables (e.g., repeatability and reproducibility; adaptive sequence generation; automated protocolling; assist with smart positioning to decrease retakes; assist with treatment planning).…”
Section: Against the Proposition: Elizabeth A Krupinski Phdmentioning
confidence: 99%
“…Jika masih memiliki kelebihan energi setelah itu, sinar gamma dipancarkan untuk mencapai steady state. 5,6 Radiasi partikel Radiasi partikel adalah radiasi yang terdiri dari partikel atom atau subatomik (elektron dan proton) yang membawa energi dalam bentuk energi kinetik atau massa yang bergerak. 6 Radiasi partikel terdiri dari elektron, proton dan neutron beams.…”
Section: Radiasi Elektromagnetikunclassified
“…Biasanya digunakan dalam terapi radiasi sehari-hari dan sangat berguna pada terapi tumor yang dekat dengan permukaan tubuh karena tidak menembus ke dalam jaringan. 6,7 Proton beams merupakan radiasi partikel yang lebih baru digunakan untuk mengobati kanker. Radiasi ini memiliki distribusi dosis yang lebih baik karena profil penyerapannya yang unik dalam jaringan yang dikenal sebagai puncak Bragg (Bragg peak) sehingga memungkinkan terjadi pengendapan energi destruktif dengan maksimal di lokasi tumor dan meminimalkan kerusakan pada jaringan sehat di sepanjang jalur kerjanya.…”
Section: Radiasi Elektromagnetikunclassified
“…Thus, radiotherapy is valuable in tumour treatment. With the widespread use of precise radiotherapies, including conformal radiotherapy, intensity-modulated radiotherapy, image-guarded radiation therapy, and the application of protons and heavy ions in the clinic, the role of radiotherapy has become increasingly important in tumour therapy ( 6 ). However, in clinical practice, the majority of radiation practitioners have found that not every patient with a tumour responds to the treatment ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%